Stress and deformation heterogeneity in individual grains within polycrystals subjected to fully reversed cyclic loading. (June 2015) - Wong, Su Leen; Obstalecki, Mark; Miller, Matthew P.; Dawson, Paul R.
Abstract: The influence of spatial variability of the crystal stresses on the evolution of intragrain lattice misorientations during cyclic loading of a polycrystalline copper alloy is examined using a combination of simulation and experiment. The experiments consist of measuring the mechanical responses of deforming individual crystals using high-energy x-ray diffraction and in situ mechanical loading. The simulations employ a crystal-based finite element formulation which is used to compute stress distributions and lattice reorientations in virtual polycrystals subjected to the same loading history. The hybrid methodology produces a picture of the evolving microstructural state during cyclic plasticity. For four target grains, comparisons are made between the diffracted peak intensity distributions as recorded by the experimental detector and those computed from simulation using a virtual diffractometer. Based on the comparisons, a relationship is presented between intragrain lattice misorientations and broadening of the diffraction peaks from individual grains. Stress triaxiality within grains is examined and regions with positive triaxiality throughout the tension/compression loading history are identified as potential locations for void growth.